Professionalism and campus police officers - Foster, Julia A. (American journal of criminal justice, 1986)
Survey research was conducted to examine the effects of education, perceptions of community attitudes, and career commitment upon overall job satisfaction of campus law enforcement officers in North Carolina. Thirteen (13) campus departments participated in the 1984 study. Findings revealed both significant and insignificant relationships. The attained level of post-secondary education was not significantly related to an officer’s perception of having his/her authority questioned, nor was education related to an officer’s feeling of boredom with the job. However, significant relationships were found between several variables including an officer’s willingness to recommend the job to another person and his/her perceptions of community attitudes and the rank of the officer and his/her commitment to the current position.(1)